Impact of self-reported SARS-CoV-2 antibody positivity on cardiac structure and function: findings from UK Biobank CMR cohort - Chang Liu; Yao Ma; Shiyuan Qiao; Kexin Li; Mengyao Qi; Chunyu Gu; Chunyu Gu; Lanxin Zhang; Lanxin Zhang; Jia Wei; Dengfeng Gao (Frontiers in Cardiovascular Medicine)
BackgroundSARS-CoV-2 antibody positivity, whether due to natural infection or vaccination, is known to be associated with specific cardiac and vascular damage, yet its impact on cardiac structure and function in prospective cohorts remains incompletely understood.ObjectiveWe aimed to assess cardiac changes in the UK Biobank cohort among individuals with self-reported seropositive results for SARS-CoV-2 antibodies.MethodsUK Biobank participants with self-reported serological results for SARS-CoV-2 antibodies, who underwent their first cardiac magnetic resonance (CMR) scan after 2019 were included. Cardiac changes potentially associated with SARS-CoV-2 antibody positivity were assessed, with measurements of left ventricular (LV) parameters, including volume, dimensions, wall thickness, myocardial mass, cardiac output (CO), and cardiac index (CI), manually extracted from the CMR images. Propensity score matching (PSM) was used to pair seropositive and seronegative individuals. Native T1 was used to assess the within-subject changes in seropositive individuals. Logistic regression was performed to assess the association between SARS-CoV-2 antibody status and the incidence of LV hypertrophy.ResultsA total of 720 participants were included, with 453 individuals self-reporting as SARS-CoV-2 antibody positive. After PSM, 261 participants remained in each group. Over an average follow-up period of 110 days, significant decreases in CO and CI were observed in the paired participants. Additionally, native T1 values appeared to be elevated in seropositive participants (852.77 ± 53.55 ms vs. 860.01 ± 47.81 ms, P = 0.012). Logistic regression analysis in the overall cohort indicated an association between SARS-CoV-2 antibody positivity and an increased risk of LV hypertrophy, with an adjusted odds ratio of 3.257 [95% CI (1.036–10.239), P = 0.043].ConclusionsOur findings suggest subtle cardiac changes associated with SARS-CoV-2 antibody positivity within approximately hundred days. SARS-CoV-2 antibody positivity appeared to be associated with an increased risk of LV hypertrophy. However, these results are exploratory, and further longitudinal studies with extended follow-up are needed to better understand the long-term cardiac impact of SARS-CoV-2 antibody positivity.